Perbandingan Pendapatan Peternak Ayam dan Industri Rumah Tangga (Industri Purun) terhadap Permodalan PUAP Di Desa Panyaungan Kecamatan Amuntai Utara Kabupaten Hulu Sungai Utara - Rachman Fitriannor; Muzalifah Muzalifah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2019)
This study aims to find out (i) the total income obtained by respondents seeking broiler chicken livestock (ii) the total income obtained by respondents seeking purun woven industry, (iii) the amount of difference in total income obtained by respondents seeking broiler chickens, with those strive for purun plaited household industry. The results showed that: total costs for broiler chicken farming conducted by respondents in Panyaungan Village, North Amuntai Sub-District, Hulu Sungai Utara Regency, averaged Rp.21,004,932.10. With details of the average cost of fixed costs of Rp.577,744, 60 / period of maintenance and the average variable costs reached Rp.20,427,187.50 / maintenance period. Average revenue of Rp. 23,307,375.00 / peroide of maintenance, with an average profit reaching Rp.2,302,443.00 / maintenance period. While respondents who sought purun matting, the total cost incurred averaged Rp2,053,134.70. Average fixed costs incurred reached Rp.828,010.00 / month, and the average variable costs incurred reached Rp.1,225,125.00 / month. The average income reaches Rp.2,250,000.00 / month, and the average profit obtained reaches Rp.196,685.00 / month. Broiler chicken and purun matting are feasible, because the RCR value of the two types of business is> 1. The RCR value of broiler chicken farming reaches 1,107 and the RCR value of purun plait business reaches 1,096. Thus the farming that is held is feasible to be cultivated, because every sacrifice of Rp. 1.00 will produce Rp. 1,107 and Rp. 1,096.